Association of long-term exposure to PM2.5 and survival following ischemic heart disease - Oh, Jongmin; Choi, Sangbum; Han, Changwoo; Lee, Dong Wook; Ha, Eunhee; Kim, Soontae; Bae, Hyun Joo; Pyun, Wook Bum; Hong, Yun Chul; Lim, Youn Hee (Environmental Research, 2023)
Background: Numerous studies have suggested that long-term exposure to particulate matter ≤2.5 μm (PM2.5) may cause cardiovascular morbidity and mortality. However, susceptibility among those with a history of ischemic heart disease is less clearly understood. We aimed to evaluate whether long-term PM2.5 exposure is related to mortality among patients with ischemic heart disease. Methods: We followed up 306,418 patients hospitalized with ischemic heart disease in seven major cities in South Korea between 2008 and 2016 using the National Health Insurance Database. We linked the modeled PM2.5 data corresponding to each patient's administrative districts and estimated hazard ratios (HRs) of cause-specific mortality associated with the long-term exposure to PM2.5 in time-varying Cox proportional hazard models after adjusting for individual- and area-level characteristics. We also estimated HRs by sex, age group (65–74 vs. ≥75 years), and household income. Results: Of the patients with ischemic heart disease, mean age at the discharge was 76.8 years, and 105,913 died during a mean follow-up duration of 21.4 months. The HR of all-cause mortality was 1.10 [95% confidence intervals (CI): 1.07, 1.14] per 10 μg/m3 increase in a 12-month moving average PM2.5. The HRs of cardiovascular, stroke, and ischemic heart disease were 1.17 (95% CI: 1.11, 1.24), 1.17 (95% CI: 1.06, 1.30), and 1.25 (95% CI: 1.15, 1.35), respectively. The subgroup analyses showed that participants aged 65–74 years were more susceptible to adverse effects of PM2.5 exposure. We did not observe any differences in the risk by sex and household income. Conclusion: Mortality from all-cause and cardiovascular disease following hospitalization due to ischemic heart disease was higher among individuals with greater PM2.5 exposure in seven major cities in South Korea. The result supports the association of long-term exposure to air pollution with poor prognosis among patients with ischemic heart disease.
Keywords: Air Pollutants; Air Pollution; Cardiovascular Diseases; Cohort Studies; Environmental Exposure; Humans; Myocardial Infarction; Myocardial Ischemia; Particulate Matter; Cohort studies; Ischemic heart disease; Mortality; Particulate matter; Survival analysis